INITIAL PUBLIC OFFERING (IPO) OF CAPITAL MARKET AND CAPITAL MARKET COMPANIES IN INDONESIA - Hartana, Hartana (Ganesha Law Review, 2019)
From the aspect of Capital Market Law, the Initial Public Offering (IPO) conducted by PT. Dian Swastatika Sentosa Tbk (PT. DSS Tbk) is legitimate and has complied with all the provisions governing this matter. This can be seen in a series of stages of the IPO implementation carried out by PT. DSS Tbk. Likewise, if viewed from the legal aspects of Mineral and Coal Mining, it does not indicate any contradiction with the article governing Coal Mining if it is associated with the IPO process of PT. DSS Tbk. In conducting the IPO, PT. DSS Tbk does not experience significant obstacles. The only obstacles faced are small bureaucratic obstacles and policies can be overcome by the active role of Bapepam-LK. This shows that Bapepam-LK has acted as a dynamic supervisor.